Radios for farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Before, when animals got lost there was virtually no chance of finding them. Now that we have our radio, we can issue a simple alert for FCFA100 (less than 0.20) and, very soon, you have your animal back explains one Nigerian livestock farmer